Acute and long‐term results of carotid stenting under proximal embolic protection using the gore flow reversal system1. Issue 1 (19th November 2012) - Bode, A.; Franke, J.; Rabe, K.; Hornung, M.; Wunderlich, N.; Bertog, S. C.; Sievert, H.
Abstract Objective This study evaluates short‐ and long‐term results of CAS with the Gore Flow Reversal System (GFRS). Background Embolic protection devices are of fundamental importance in carotid artery stenting (CAS). Proximal protection has potential advantages compared with distal protection. Limited data are available regarding the safety of the proximal GFRS. Methods CAS was performed with the GFRS. Patients' neurological status was assessed during the intervention and at follow‐up. Results of patients treated before 2006 were also compared to those of patients treated after 2006 because of changes in device design. Results CAS was performed in 86 patients with 87 stenoses (symptomatic in 37%). The procedure was technically successful in all cases. In 11 patients a transient periprocedural neurologic deficit occurred related to temporary cerebral flow compromise during balloon occlusion with complete resolution at completion of the procedure. The stroke/death rate at one month was 2.3% with a combined ipsilateral stroke and death rate at one year of 4.6%. There was no significant difference in event rates between the newer and older device version. Overall follow‐up time was 484 ± 3.4 patient years with a range of 0 to 119 months. The average yearly ipsilateral stroke rate including the first 30 days was 0.96%. Conclusion Our results demonstrate that CAS using the GFRS is safe whether the original or new device versions were used. The periprocedural stroke rate is at least as low as the stroke rate reported using distal protection. The long‐term stroke rate after CAS is low. © 2012 Wiley Periodicals, Inc.